Mantra or Gimmick - Political Framing of Corporate Social Responsibility in British Newspapers - Mosonyi, Szilvia (2007)
The main objective of this study is to add to the existing research on the relationship between Corporate Social Responsibility (CSR) and media by considering news outlets that are studied by a broader public, hence have a greater impact on the public opinion. Furthermore, the purpose is to examine how the meaning of Corporate Social Responsibility is constructed through them. The paper hypothesises that this construction process is influenced partly by the political ideologies of the newspapers. The research focuses on four British quality newspapers; The Independent, The Guardian, The Times and The Telegraph. The findings of the present research enforce the claim that CSR has news value. The salience of the concept increased in the analysed newspapers in the past two decades, following the growth in academic or business papers. The term CSR was not used frequently in the first analysed period from 1988 to 1994, and other overlapping terms were more prevalent. From 2001, CSR increasingly was ascribed a differentiated meaning. However, there is no agreement in the media either on its ultimate content. The arguments presented in the newspapers were diverse, varying across time and titles. However, few common themes or frames emerged from the analysis of the most relevant articles. The issues associated with CSR increased through the years, the environment remaining the main focus. Positive and negative evaluations of CSR were balanced in these texts. However, from the analysis of ideological arguments, it became apparent that right-leaning titles ascribed ideologically framed arguments against the concept more. The research concludes that the influence of media on the proliferation of CSR is beyond question, and should be in the focus of future research.